6.7k views
3 votes
Solve:
3 = -2v - V
V=​

User Nobik
by
5.1k points

2 Answers

4 votes

Answer:

Subtract v from −2v.

Which equals −3v.

-3v = 3.

Explanation:

v = -1.

-3 x -1 = 3.

3 = 3.

Therefore, v = -1.

User Polesen
by
5.5k points
3 votes

Answer:

V = −1

Explanation:

Step 1: Simplify both sides of the equation.

3=−2v−v

3=−2v+−v

3=(−2v+−v)(Combine Like Terms)

3=−3v

3=−3v

Step 2: Flip the equation.

−3v=3

Step 3: Divide both sides by -3.

−3v = 3

-3 -3

v=−1

User Suraz
by
5.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.